EXPLORING THE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON SMART CITY INFRASTRUCTURE DEVELOPMENT - Kumala Dewi, Nurlaela (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background:The rapid urbanization of the 21st century has led to unprecedented challenges in city management and infrastructure development. Smart cities, powered by Artificial Intelligence (AI), have emerged as a transformative solution, enabling efficient resource management, sustainable growth, and improved quality of life. Aims:This study explores the influence of AI on the development of smart city infrastructure, focusing on its applications in urban planning, transportation, energy management, and public services. Research Method:A qualitative approach is employed, combining a comprehensive literature review with case studies from leading smart cities worldwide. Data were analyzed to identify key trends, challenges, and opportunities in integrating AI into urban systems. Results and Conclusion:The findings reveal that AI significantly enhances smart city infrastructure by enabling predictive analytics, real-time monitoring, and automation. However, challenges such as data privacy, ethical considerations, and implementation costs persist. The study concludes that a strategic and inclusive approach to AI integration is crucial for maximizing its potential in urban development. Contribution:This research contributes to the growing body of knowledge on AI and smart cities by providing actionable insights for policymakers, urban planners, and technologists.